Applying RANSAC algorithm for fitting scanning strips from airborne laser scanning = Wykorzystanie algorytmu RANSAC przy wpasowaniu szeregów ALS - Błaszczak-Bąk, Wioleta; Janicka, Joanna; Sobieraj-Żłobińska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
During the development of the data acquired by airborne laser scanning the important issue is the fitting and georeferencing of ALS point clouds by means of the tie surfaces and the reference planes. The process of scanning strips adjustment is based on mutual integration of point clouds (scanning strips) and their adaptation to the reference planes.
Keywords: airborne laser scanning; RANSAC algorithm; fitting; lotniczy skaning laserowy; algorytm RANSAC; wpasowanie